Strategy For Developing Digital-Based Sharia Financial Products To Improve Financial Inclusion - Mohammad Syafii Budi Santoso; Mohamad Nur Husen; Abdul Wakhid; Dimyati Dimyati (TIJAROTANA : Jurnal Ekonomi dan Bisnis Syariah, 2026)
This study aims to analyze the development strategy for digital-based Islamic financial products to increase financial inclusion. The development of digital technology has driven the transformation of the financial sector, including the Islamic financial industry. However, the level of financial inclusion in Indonesia still faces various challenges, particularly for communities that have not yet accessed formal financial services. This study uses a descriptive qualitative method with a literature study approach. The data used are secondary data obtained from scientific journals, books, and reports from relevant institutions. The data analysis technique used is content analysis. The results show that the development strategy for digital-based Islamic financial products includes digital product innovation, collaboration with fintech, increasing financial literacy, and strengthening Islamic regulations and compliance. Digital-based Islamic financial products have been proven to increase access, efficiency, and reach of financial services, thus contributing to increased financial inclusion. However, challenges remain, such as low digital literacy, security issues, and limited infrastructure. Therefore, synergy between financial institutions, regulators, and the public is needed to optimize the potential of Islamic financial digitalization